2021
DOI: 10.7554/elife.59291
|View full text |Cite
|
Sign up to set email alerts
|

AAV ablates neurogenesis in the adult murine hippocampus

Abstract: Recombinant adeno-associated virus (rAAV) has been widely used as a viral vector across mammalian biology and has been shown to be safe and effective in human gene therapy. We demonstrate that neural progenitor cells (NPCs) and immature dentate granule cells (DGCs) within the adult murine hippocampus are particularly sensitive to rAAV-induced cell death. Cell loss is dose dependent and nearly complete at experimentally relevant viral titers. rAAV-induced cell death is rapid and persistent, with loss of BrdU-la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 104 publications
(172 reference statements)
2
34
0
Order By: Relevance
“…We confirmed this through control injections of PHP.B/hSYN-EGFP, whereby hippocampal EGFP overexpression resulted in a similar lesion. As was recently shown, AAV internal terminal repeat sequences are themselves sufficient to mediate dose-dependent toxicity and cell death in the hippocampus, preferentially in dentate gyrus neural progenitor cells (70). This is a plausible mechanism to explain the dentate gyrus lesions we observed in our study and should serve as a cautionary tale for gene therapy approaches that expose the hippocampal neurogenic niche to high doses of AAV.…”
Section: Discussionsupporting
confidence: 80%
“…We confirmed this through control injections of PHP.B/hSYN-EGFP, whereby hippocampal EGFP overexpression resulted in a similar lesion. As was recently shown, AAV internal terminal repeat sequences are themselves sufficient to mediate dose-dependent toxicity and cell death in the hippocampus, preferentially in dentate gyrus neural progenitor cells (70). This is a plausible mechanism to explain the dentate gyrus lesions we observed in our study and should serve as a cautionary tale for gene therapy approaches that expose the hippocampal neurogenic niche to high doses of AAV.…”
Section: Discussionsupporting
confidence: 80%
“…To rule out the possibility that AAV toxicity ( Johnston et al, 2021 ) restrained the AtoN conversion process, we synthesized antisense oligonucleotide (ASO) against mouse Ptbp1 as an alternative strategy for PTBP1 repression ( Figure 4A ). Immunofluorescence results showed that ASO was distributed broadly in the midbrain, as indicated by ASO-attached Cy3, and astroglial PTBP1 was significantly downregulated for 2 months after ASO- Ptbp1 delivery compared to ASO-Ctrl delivery ( Figure 4—figure supplement 1A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that AAV can exert toxic effects on doublecortin (DCX) + neuroblasts or neural progenitor cells ( Johnston et al, 2021 ), which might render the virus-infected astrocytes unable to convert into neurons. After reviewing previous studies of in vivo glia-to-neuron conversion, we found that DCX + intermediate cells could hardly be detected using AAV for gene manipulation ( Liu et al, 2015 ; Guo et al, 2014 ; Brulet et al, 2017 ; Mattugini et al, 2019 ; Chen et al, 2020 ; Lai et al, 2020 ; Leib et al, 2022 ; Liu et al, 2020 ; Xiang et al, 2021 ; Zheng et al, 2022 ; Torper et al, 2015 ; Pereira et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used transsynaptic viruses such as rabies virus, pseudorabies virus, and VSV all have notable cytotoxic effects that prevent the normal function of neurons. Even relatively benign viruses such as AAV can induce cell death and alter neuronal activity and neurogenesis (Johnston et al, 2021 ). Notably, a recent study has shown that a different VSV variant (R7A mutation in the VSV-N protein) may have reduced toxicity and enhanced anterograde spread in mice (Lin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%